KEWENANGAN PEMERINTAH DAERAH KABUPATEN BADUNG MEMUNGUT BEA PEROLEHAN HAK ATAS TANAH DAN BANGUNAN - Ketut Sista Putri Wijaya; A. A. Gde Oka Parwata (Kertha Negara : Journal Ilmu Hukum, 2014)
Customs Acquisition of Land and Building (BPHTB) is one type of tax potential in the Badung regency especially with the tourism industry and the utilization of very developed land and buildings. Based on the Act No. 28 Year 2009 on Regional Tax and Levies, hence it the district/city in this paper especially Badung regency has the authority to levy BPHTN. With the methods and approaches of writing normative law, this paper describes the arrangement of BPHTB and also the authority of Badung regency to levy BPHTB conducted by Revenue Office of Badung regency.